Levers of control and psychological mechanisms: insights from an individual-level perspective - Noor Hasniza Haron; Norhayati Alias; Tuan Zainun Tuan Mat; Mazurina Mohd Ali (International Journal of Accounting, Finance and Business, 2026)
This paper reviews and synthesizes literature examining how Levers of Control namely the belief systems, boundary systems, diagnostic controls, and interactive controls can influence individual-level psychological and behavioural outcomes. This paper analyses the psychological mechanisms through which control systems shape employee experiences, including empowerment, motivation, sensemaking, role clarity, emotional responses, and stress. The synthesis reveals that belief and interactive controls are most consistently associated with positive psychological outcomes such as empowerment, creativity, learning, and proactive behaviour. In contrast, boundary and diagnostic controls have primarily been studied in relation to compliance and performance, with limited attention to their deeper psychological consequences. Notably, negative individual-level effects including stress, reactance, pressure, and moral disengagement remain largely unexplored across all levers. Based on these insights, the paper identifies key gaps and proposes a research agenda emphasizing the need to investigate psychological effects of boundary and diagnostic controls, explore underexamined mechanisms such as emotions and intrinsic motivation, integrate multiple levers to examine their joint influence, employ longitudinal and experimental designs to establish causal pathways, and incorporate contextual and individual differences. By foregrounding psychological processes, the paper contributes to a more comprehensive micro-foundational understanding of management control systems and their influence on cognition, motivation, and behaviour in organizational settings.